Factors Influencing Purchase Intention and Purchase Decision in Health Services at Zona.Gizi - Ekaputra, Rismoyo; Bangsawan, Satria; Fihartini, Yuniarti (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the influence of price perception, brand image, service quality, promotion, perceived ease of use, and perceived usefulness on purchase intention and purchase decision of Zona Gizi health services. The research was conducted on 358 respondents selected based on their experience and knowledge regarding Zona Gizi services. The questionnaires were distributed both directly using a survey method and via Google Form links shared through WhatsApp and Instagram social media platforms. The data analysis technique used in this study was Structural Equation Modeling (SEM) operated through IBM SPSS AMOS 21 software. The results show that the variables of price perception, brand image, service quality, promotion, perceived ease of use, and perceived usefulness have a significant positive effect on the purchase intention of Zona Gizi health services. Furthermore, purchase intention has a significant positive influence on the purchase decision of Zona Gizi health services.